Profil Berpikir Kreatif Siswa pada Mata Pelajaran Matematika SD Kelas 4 - Wahyu Susiloningsih; Hanim Faizah; Eko Sugandi (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article describes an overview of the fourth grade students' thinking ability. Creative thinking is a skill needed to solve various problems that continue to grow and change. Creative thinking skills are needed to deal with various problems in the future. Creativity is the ability to bring up new ideas or ideas to existing or never existing inventions to solve a problem. Based on the results of this literature review, it was found that creative thinking skills need to be given to students from an early age. Mathematics learning should include activities that foster creative. Creative thinking skills can be identified in high, medium, and low categories in order to develop students' creative thinking skills through several learning activities. To find out these categories, further research can be carried out.